Ketimpangan Ekonomi dan Sosial yang Terjadi pada Masyarakat di Wilayah Wara Kota Palopo - Ernawati; Muh. Rasbi; Wulandari; M. Aditia Asri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
issue that affects the welfare of the local community. Even though Palopo City has experienced several developments, the Wara region still faces significant challenges related to unequal distribution of income, access to education, health and infrastructure. This article aims to analyze the factors that cause inequality, its impact on society, and efforts that can be made to reduce this gap. The main factors causing inequality in Wara include limited access to education and skills training, limited economic opportunities in the informal sector, and underdeveloped infrastructure. The impacts of this inequality include increasing social inequality, hindering sustainable development, and worsening poverty levels. To overcome this problem, increasing access to education, equitable infrastructure development, local economic empowerment and efforts to eliminate social discrimination are needed. With collaborative efforts between the government, the private sector and the community, it is hoped that economic and social inequality in the Wara region can be reduced, bringing positive impacts to community welfare and inclusive development.